GENRES EXPRESSING THE CONCEPT OF APPEAL IN LYRIC POETRY (BASED ON THE WORKS OF XALIMA XUDOYBERDIYEVA, ZEBO MIRZO, ZULFIYAXONIM ISROILOVA, XALIMA AHMEDOVA, AND SAIDA ZUNUNOVA) - Nabiyeva Nodira Saidovna (Western European Studies, 2025)
This article examines the lyrical genres that express the concept of appeal in Uzbek poetry, particularly through the works of female poets such as Xalima Xudoyberdiyeva, Zebo Mirzo, Zulfiyaxonim Isroilova, Xalima Ahmedova, and Saida Zununova. The study highlights how different poetic forms, including supplication, lament, and invocation, serve as a means for poets to convey deep emotions, devotion, and spiritual longing. By analyzing the works of these poets, we explore how appeal is interwoven with themes of love, fate, and faith, reflecting the unique sensitivity and inner world of women’s poetry.
Keywords: Appeal; lyrical poetry